Primary extraovarian adult granulosa cell tumor of the greater omentum: a case report and literature review - Zeng, Ying; Lv, Liang; Luo, Liping (Frontiers in Oncology, 2026)
Extraovarian adult granulosa cell tumors are rare. The diagnosis of extraovarian adult granulosa cell tumors is challenging. Here we presented a case of extraovarian adult granulosa cell tumor originating in the greater omentum. Along with a review of the literature, we aim to summarizes its clinicopathological features to enhance recognition of this tumor. A 55-year-old female patient presented with dull abdominal pain for 3 days. Abdominal CT revealed a soft tissue density mass in the right lower abdomen, measuring 9.0 × 6.3 × 6.0 cm. The mass demonstrated an regular contour and indistinct borders, with heterogeneous density. Histopathological examination revealed a tumor encapsulated by a fibrous capsule. The tumor cells were arranged in cords and trabeculae with a streaming pattern. Call-Exner bodies were identified. The tumor was composed of round, oval, or polygonal cells. Nuclear grooves and “coffee-bean” nuclei were observed. The mitoses figures was 1 mitoses per 10 high-power fields (HPFs, 40×objective, field area = 0.237 mm²). Tumor cells were positive for α-inhibin, SF-1, FOXL2, WT-1, and Vimentin. The Ki67 proliferation index was 20%. The histological morphology and immunophenotype support the diagnosis of adult granulosa cell tumor. Furthermore, intraoperative abdominal exploration and imaging studies revealed no lesion in the uterus or bilateral adnexa. Therefore, the diagnosis of an extraovarian adult granulosa cell tumor was established. Extraovarian granulosa cell tumors occur predominantly in middle-aged women, most commonly in the retroperitoneum, and typically present as large cystic-solid masses. The diagnosis of extraovarian granulosa cell tumor requires the definitive exclusion of a primary ovarian tumor. Diagnosis primarily relies on characteristic histomorphological features supported by immunohistochemical staining, notably positivity for markers such as α-inhibin. In diagnostically challenging cases, FOXL2 mutation testing can serve as a valuable ancillary tool to confirm the diagnosis. Surgical resection is the mainstay of treatment in most cases. Consequently, we recommend that all patients with primary extra-ovarian granulosa cell tumors enter a protocol of long-term surveillance, including periodic imaging and hormonal marker assessment.